The Implications Of CSR And GCG On Tax Avoidance - R. Rosiyana Dewi; Itjang D Gunawan (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2019)
The disclosure of a company's social responsibility (CSR) showed how much the company has a motive for its environmental welfare; a company that has high responsibility prevents violations that have a negative impact on their environment, including tax evasion. This study aims to examine the effect of CSR disclosure on tax avoidance and test the GCG component, audit committee and independent commissioners in moderating the effect of CSR on tax avoidance. The study population was manufacturing companies listed on the Indonesia Stock Exchange in 2012-2015. Samples were obtained using a purposive sampling method with 108 samples. This research is quantitative research. The research test uses multiple regressions, such as goodness of fit test and hypothesis test. This study provides evidence that there is a positive influence between CSR on tax avoidance, besides that the audit committee as a moderating variable weakens the positive influence of CSR on tax avoidance, but independent commissioners are not proven as moderating variables between the effects of CSR towards tax avoidance.